Online Shopping Behaviour: A Study on Exploring the Dependence of Demographics of the People in Kerala on their Behaviour in Online Shopping - et. al., Adarsh Nampoothiri S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The goal of this study is to see how the sociodemographic factors (gender,age, income, education,region) affect people’s attitudes toward online shopping in Kerala.Consumers go through an online shopping process when they decide to shop on the internet.Shopping on the internet has become one of the most prominent uses of the Internet, along with looking for products and collecting knowledge about them.The necessity of evaluating and defining factors that affect a consumer’s decision to buy something on the Internet cannot be overstated. Since the Internet is a modern medium, consumers have put forward new demands. Analyzing the actions that an online shopper takes to make a decision and buy on the internet reveals some of the considerations that they consider. In order to meet customer demands and compete in the online market, online retailers must identify and consider these factors. The aim of this dissertation was to see if there are any specific factors that affect online shoppers. An online survey was conducted among the people of Kerala to examine their online shopping behavior.